Paradoxical impact of memory on color appearance of faces - Maryam Hasantash (Nature Portfolio, 2019)
What is the function of color vision? Here, the authors show that when retinal mechanisms of color are impaired, memory has a paradoxical impact on color appearance that is selective for faces, providing evidence that color contributes to face encoding and social communication.